Non‐immunological biomarkers for assessment of villous abnormalities in patients with celiac disease. Issue 3 (30th October 2019) - Singh, Alka; Verma, Anil K; Das, Prasenjit; Prakash, Shyam; Pramanik, Raja; Nayak, B; Datta Gupta, Siddhartha; Sreenivas, V; Kumar, Lalit; Ahuja, Vineet; Makharia, Govind K
Abstract: Background and Aim: Demonstration of villous abnormalities is an essential component of diagnosis of celiac disease (CeD) that requires duodenal biopsies. There is a need for non‐invasive biomarker(s) that can predict the presence of villous abnormalities. Methods: Levels of plasma citrulline, plasma intestinal fatty acid binding protein (I‐FABP), and serum regenerating gene 1α (Reg1α) were estimated in treatment naïve patients with CeD and controls. The levels of these biomarkers and their cyclical pattern were validated in a predicted model of enteropathy. Optimum diagnostic cut‐off values were derived, and the results were further validated in a prospective validation cohort. Results: While level of plasma citrulline was significantly lower, the levels of plasma I‐FABP and serum Reg1α were significantly higher in patients with CeD ( n  = 131) in comparison with healthy ( n  = 216) and disease controls ( n  = 133), and their levels reversed after a gluten‐free diet (GFD). In the model of predicted enteropathy ( n  = 70), a sequential decrease and then increase in the level of plasma citrulline was observed; such a sequential change was not observed with I‐FABP and Reg1α. The diagnostic accuracy for prediction of presence of villous abnormality was 89% and 78% if citrulline level was  ≤ 30 μM/L and I‐FABP levels were ≥ 1100 pg/mL, respectively. The results were validated in a prospective validation cohort ( n  = 104) with a sensitivity and specificity of 79.5% and 83.1%, respectively, for predicting villous abnormalities of modified Marsh grade >  2 at calculated cut‐off values of citrulline and I‐FABP. Conclusions: Plasma citrulline  ≤ 30 μM/L is the most consistent, highly reproducible non‐invasive biomarker that can predict the presence of villous abnormality and has the potential for avoiding duodenal biopsies in 78% patients suspected to have CeD.